Efficacy of cassava by-products as carrier materials of Trichoderma harzianum, a biocontrol agent against Sclerotium rolfsii causing collar rot in Amorphophallus. - John, Neetha; Anjanadevi, Indira P; Jeeva, Muthulekshmi L (JOURNAL OF ROOT CROPS, 2015)
The ability of cassava (Manihot esculenta Crantz) by-products such as cassava leaf powder, cassava seed oil and cassava thippy as carrier materials to preserve the viability and antagonistic potential of Trichoderma harzianum, a potent strain against Sclerotium rolfsii was investigated during February 2011 to August 2012 at Central Tuber Crops Research Institute, Thiruvananthapuram, India. The shelf life period of Trichoderma harzianum was highest for cassava seed oil (1x106 cfu ml-1) without severe reduction in the initial population at the end of incubation period of 18 months, which fulfills the minimum recommended population of fungal bioagent in any formulation for seed treatment, while cassava leaf powder maintained the recommended population for nine months. The inhibitory effect of T. harzianum against tested pathogenic fungi was maximum when stored in cassava seed oil (81.57%) than cassava leaf powder (79.2%) after 18 months. The study indicated that T. harzianum mixed in cassava seed oil had the longest shelf-life and antagonistic activity extending to more than an year, whereas this was least for the antagonist formulated in cassava thippy.